Snowball Throwing Learning Model On Learning Activeness Students In Language Subjects English In Class VII C SMP Negeri 5 Palopo - Husnani Aliah; Jusriati Jusriati; Anil Anil (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The goal to be achieved in this research is to find out the effectiveness of the snowball throwing learning model for the learning activities of class VII C students of SMPN 05 Palopo. This research used pre-experimental research, namely the type of One-Group Pretest-Posttest Design. In this research, the researchers did the research for 6 meetings. With this research, the results of the treatment can be known more accurately, because it can be compared with the conditions before being given treatment (treatment) and after being given treatment. Based on the results of the research, the use of the snowball throw learning method is effectively used to support students' active learning in the classroom. The application of the learning method of throwing snowballs in class VII C of SMPN 05 Palopo in the English subject has increased rapidly. This research was conducted in 2 (two) stages, namely pretest and posttest. The pretest was carried out before applying the snowball throw learning method to see students' interaction skills in class, and the results of class VII C's pretest were in the less active category. While the posttest or the application of the snowball throwing learning method in the teaching and learning process, the posttest results are in the very good category.